Patterns of condom use and associated factors among adult HIV positive clients in North Western Ethiopia: a comparative cross sectional study - Yalew Estifanos; Zegeye Desalegn T; Meseret Solomon (BMC, 2012)
Abstract Background The introduction of antiretroviral therapy (ART) has sharply decreased morbidity and mortality rates among HIV infected patients. Due to this, more and more people with HIV live longer and healthier lives. Yet if they practice sex without condom, those with high viral load have the potential to infect their sero-negative sexual partner or at risk of acquiring drug resistant viral strains from their sexual partner who are already infected. Hence, we aimed to assess practice of condom use and associated factors among HIV positive clients at Felege Hiwot Referral Hospital in North Western Ethiopia. Methods Hospital based comparative cross sectional study was conducted at Felege Hiwot Referral Hospital in northwest Ethiopia. Systematic random sampling technique was used to select 466 study participants from the ART and pre ART clinic of the Hospital. A structured interview administered questionnaire first prepared in English then translated into Amharic was used to collect data. Nurses who were working in the hospital but not in the HIV clinic were recruited and trained as data collectors. Results A total of 454 (224 respondents from ART naive and 230 ART experienced groups) were included in the study. Females constitute 151 (67.4%) and 133 (57.8%) of pre ART and ART group respectively. The ages of the participants ranged from 18 to 72 years. The average age was 31.7 years for women and 36.6 years for the men. About half of the participants (47.4% of ART group and 50.4% of the pre ART group) were sexually active. Inconsistent condom use was reported by 61(56%) ART and 50 (44.2%) of the pre ART sexually active study participants. Conclusions The study found that those who are on ART were at lower risk of using condom inconsistently as compared to the ART naïve patients living with HIV. Therefore, these results are of high importance in order to design tailored interventions.